Analysis of the Electronic Implementation of A Malaria Surveillance Information System (E-SISMAL) in the Lahat District - Eni Nuraini; Hamzah Hasyim; Haerawati Idris; Ahmad Ghiffari; Chairil Anwar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: The requirement for malaria elimination to be recognized is to prove API lower than 1 per 1000 in the population, together with no indigenous case. Lahat Regency is an area of low-endemicity for malaria, where the target for elimination is projected for 2024. Since 2019, Lahat Regency has received socialization about E-SISMAL, which was developed as a web-based basis to speed up the reporting process. However, there are still delays in reporting malaria on E-SISMAL. Methods: Descriptive research with a qualitative approach was designed. The study subjects were the malaria person in charge, the head of seven selected community health centers (Puskesmas) and the Lahat District Health Office. Primary data came from observation, focus group discussion (FGD) and in-depth interviews with eighteen informants selected by the purposive sampling method. Results: The available inputs are inadequate, such as the human resource education was not up to standard, the internet network was not smooth, and there were no guidelines on E-SISMAL in the health centers. Malaria person in charge does not understand how to use E-SISMAL. In the process, there was the involvement of cross-sectoral and networked establishments. The output shows that the report indicators on E-SISMAL are not up to standard with less than 80%. Conclusions: The use of E-SISMAL in the Lahat district has not been maximized. It has an impact on delays in reporting. It is recommended that training and practice of E-SISMAL occur to improve officers' ability through socialization and that the Lahat Health Office establishes partnerships with telecommunications companies to ensure the smooth running of the network. Developing specific guidelines on E-SISMAL and a mobile phone-based malaria surveillance information system to speed up the malaria reporting process in the Lahat district is also advisable.